Predictive factors for failure of the levonorgestrel releasing intrauterine system in women with heavy menstrual bleeding - Pleun Beelen; Marian J. van den Brink; Malou C. Herman; Peggy M. Geomini; Ruben G. Duijnhoven; Marlies Y. Bongers (BMC, 2021)
Abstract Background This study was conducted to identify factors that are associated with failure of treatment using the levonorgestrel releasing intrauterine system (LNG-IUS) in women with heavy menstrual bleeding. Methods For this study, data of a cohort of women treated with an LNG-IUS was used. Women who suffered from heavy menstrual bleeding, aged 34 years and older, without intracavitary pathology and without a future child wish, were recruited in hospitals and general practices in the Netherlands. Eight potential prognostic baseline variables (age, body mass index, caesarean section, vaginal delivery, previous treatment, anticoagulant use, dysmenorrhea, and pictorial blood assessment score) were analyzed using univariable and multivariable regression models to estimate the risk of failure. The main outcome measure was discontinuation of the LNG-IUS within 24 months of follow up, defined as removal of the LNG-IUS or receiving an additional intervention. Results A total of 209 women received the LNG-IUS, 201 women were included in the analyses. 93 women (46%) discontinued LNG-IUS treatment within 24 months. Multivariable analysis showed younger age (age below 45) (adjusted RR 1.51, 95% CI 1.10-2.09, p = .012) and severe dysmenorrhea (adjusted RR 1.36, 95% CI 1.01-1.82, p = .041) to be associated with a higher risk of discontinuation. Conclusions High discontinuation rates are found in women who receive an LNG-IUS to treat heavy menstrual bleeding. A younger age and severe dysmenorrhea are found to be risk factors for discontinuation of LNG-IUS treatment. These results are relevant for counselling women with heavy menstrual bleeding.